Elongation of oligonucleotides in the 3'-direction with activated mononucleotides and their analogs using RNA ligase. - Ohtsuka, E (1980)
P1-Adenosine 5'-P2-2',3'-ethoxymethylidene nucleosides [A(5')ppN(Em)] from four common nucleosides have been prepared and used for single addition of nucleotides to elongate oligonucleotide chains in the 3'-direction in RNA ligase reaction. U-U-C, T-U-C and A-C-C were used as acceptors. Structural dependence in these acceptors was found to be smaller compared to joining reactions between oligonucleotides. Adenosine analogs including 8-bromo-, 2'-fluoro-, 2'-azido-, 8,2'-O-cyclo-, 8,2'-S-cyclo-adenosine, arabinosyladenine and 2'-deoxyadenosine were added to the 3'-end of A-C-C by adenylation chemically followed by joining with RNA ligase. Symmetrical 5'-pyrophosphates of 8-bromo-, 2'-fluoro- and 2'-azido-adenosine were not recognized as donor substrates.